A highly efficient procedure for site-specific mutagenesis of full-length plasmids using Vent DNA polymerase. - Byrappa, S; Gavin, D K; Gupta, K C (Genome Research, 1995)
Careful titration of Vent polymerase activity allows efficient amplification of full-length plasmids (12 kb). The high processivity and fidelity of this enzyme made oligonucleotide-directed site-specific mutagenesis of plasmids a straight-forward process. Using only two primers, a mutagenic and a complementary, single-base mutants of recombinant plasmids were obtained consistently with > 90% efficiency from a single round of PCR. This procedure also made site-specific deletion, insertion, and several bases mutagenesis facile and efficient.